ACoRN : acute care of at-risk newborns : a resource and learning tool for health care professionals - E. Boulton, Jill; Coughlin, Kevin; O'Flaherty, Debra; Solimano, Alfonso, 1950- (New York, NY : Oxford University Press, 2021)
The Acute Care of at-Risk Newborns (ACoRN) program trains health care providers to stabilise that most challenging and enigmatic of medical patients: the unwell newborn. The ACoRNS pneumonic defines stabilisation steps and chapter structure: Alerting Signs, Core Steps, Organisation of Care, Response, Next Steps, and Specific Diagnosis and Management. Each chapter in this book includes educational objectives, key concepts, learning points, and at least one case scenario with questions and answers to reinforce content and learnings.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 17, 2021).
Keywords: Neonatal intensive care; Newborn infants -- Medical care; Newborn infants -- Diseases